2016
DOI: 10.1007/s10461-016-1560-1
|View full text |Cite
|
Sign up to set email alerts
|

Late Diagnosis Due to Missed Opportunities and Inadequate Screening Strategies in HIV Infected Mexican Women

Abstract: Late diagnosis of HIV remains a public health issue in Mexico. Most national programs target high-risk groups, not including women. More data on factors associated with late diagnosis and access to care in women are needed. In 2012-2013, Mexican women recently diagnosed with HIV were interviewed. Socio-cultural background, household-dynamics and clinical data were collected. Of 301 women, 49 % had <200 CD4 cells/mm, 8 % were illiterate, 31 % had only primary school. Physical/sexual violence was reported by 47/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
1
14
0
6
Order By: Relevance
“…That prevalence, when using national surveys and census as a comparator, seemed higher than the prevalence reported in the general population of women. [13] There are no published studies comparing HIV-positive with HIV-negative women in Mexico. One study compared gender differences between HIV-positive men and women in Mexico City and found that in general, women had less years of schooling than men, lower average monthly salaries, and they were more likely to have been infected by a stable partner than men.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That prevalence, when using national surveys and census as a comparator, seemed higher than the prevalence reported in the general population of women. [13] There are no published studies comparing HIV-positive with HIV-negative women in Mexico. One study compared gender differences between HIV-positive men and women in Mexico City and found that in general, women had less years of schooling than men, lower average monthly salaries, and they were more likely to have been infected by a stable partner than men.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the fact that HPV infection and other STD are clearly described as risk factors associated with acquiring HIV, many studies have also described STD clinics as an opportunity to improve prevention and early diagnosis, since these clinics are the main contacts with medical services in young women. [13,25] It has been reported that women tend to have more medical contacts than men, through family planning and screening for cervical and breast cancer. This should be an opportunity to extend HIV test offer and improve HIV detection in women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus likely that a person with HIV initiating ARV at a late phase of infection will recover CD4 T cells deficiently. This is aggravated by the high rate of late diagnosis in different countries and regions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%